EBV LMP1-C terminal binding affibody molecule downregulates MEK/ERK/p90RSK pathway and inhibits the proliferation of nasopharyngeal carcinoma cells in mouse tumor xenograft models - Guo, Yanru; Kamara, Saidu; Zhang, Jing; Wen, He; Zheng, Maolin; Liu, Ying; Zhou, Luqi; Chen, Jun; Zhu, Shanli; Zhang, Lifang (Frontiers in Cellular and Infection Microbiology, 2023)
Nasopharyngeal carcinoma (NPC), is an Epstein-Barr virus (EBV) associated malignancy most common in Southern China and Southeast Asia. In southern China, it is one of the major causes of cancer-related death. Despite improvement in radiotherapy and chemotherapy techniques, locoregional recurrence and distant metastasis remains the major causes for failure of treatment in NPC patients. Therefore, finding new specific drug targets for treatment interventions are urgently needed. Here, we report three potential ZLMP1-C affibody molecules (ZLMP1-C15, ZLMP1-C114 and ZLMP1-C277) that showed specific binding interactions for recombinant and native EBV LMP1 as determined by epitope mapping, co-localization and co-immunoprecipitation assays. The ZLMP1-C affibody molecules exhibited high antitumor effects on NPC-positive cell lines and displayed minimal cytotoxicity towards NPC-negative cell line. Moreover, ZLMP1-C277 showed higher antitumor efficacy than ZLMP1-C15 and ZLMP1-C114 affibody molecules. The ability of ZLMP1-C277 decrease the phosphorylation levels of up-stream activator phospho-Raf-1(Ser338), phospho-MEK1/2(Ser217/Ser221), phospho-ERK1/2(Thr202/Thr204), thereby leading to downstream suppression of phospho-p90RSK(Ser380) and transcription factor c-Fos. Importantly, tumor growth was reduced in tumor-bearing mice treated with ZLMP1-C277 and caused no apparent toxicity. Taken together, our findings provide evidence that ZLMP1-C277 as a promising therapeutic agent in EBV-associated NPC.